Pengembangan Modul Praktikum Fisika Dasar Digital pada Materi Listrik Magnet sebagai Upaya Adaptasi Kebiasaan Baru - Rodhotul Muttaqin; Natalia Erna Setyaningsih; Upik Nurbaiti (Jurnal Pengelolaan Laboratorium Pendidikan, 2023)
Online practicum is one of the learning solutions during the pandemic but requires adjustments both in terms of material and practicum modules. The purpose of this study was to develop a Digital Fundamental physics Practicum Module on Electromagnetic Materials. The module developed is in the form of a digital module for Fundamental physics Practicum assisted by an integrated practicum video. The Research and Development Model chosen is  a    4-D Development Model which has four process stages, namely Define, Design, Development, and Disseminate. The results of the validation of the material experts obtained that the coverage and accuracy aspects of the material obtained a percentage score of 80% and the aspect of material recency received a score of 93%. The results of the validation of linguists found that aspects of language suitability and communicative use of language obtained a percentage score of 93%. In addition, the aspect of using language that stimulates student curiosity has a score of 80%. The results of media expert validation found that the media presented in the digital practicum module had the accuracy of using media in the form of images and videos, aesthetics in images and videos, as well as a clear and systematic description of video interpretation with an average score of 93%. The feasibility test resulted in an average percentage score of 86%, this means that the module is in the very feasible category